The methodological aspects of Feliks Koneczny’s conception of a philosophy of history - Bukowska, Sonia (Folia Philosophica, 2000)
The subject of the article is the position of Feliks Koneczny (1862-1949), a Polish historian and a philosopher of history, towards the methods of pursuing a philosophy of history. A presentation of his stance was preceded by a short outline of the situation in the philosophy of history at the turn of the 20th c. with a special emphasis on the innovative trends that arose at that time and the proponents of which strove to revise the traditional methods of historical research. The author touches on Koneczny’s views on the problem of the usefulness of the conservative methods of studying history in constructing historical and philosophic syntheses. He also analyses the said scholar’s attitude towards both the inductive and deductive method, and presents Koneczny’s proposal for a methodological compromise.